Susciter un changement politique à Cuba par le numérique : le projet ZunZuneo de l’USAID - Tristan MATTELART (Tic & Société)
While there is extensive literature that analyzes how activist groups use digital technologies for circumventing the censorship policies implemented by authoritarian regimes, less attention has been given to the ways in which some States use these technologies for exerting, from the outside, a political influence on these regimes. In this article, we study the case of ZunZuneo, a project which was developed, between 2009 and 2012, by the United States Agency for International Development (USAID), aiming at creating an alternative communication network in Cuba. First, we show how, as from the beginning of the 1990s, the rise of digital technologies has been seen by Washington as a tool for fomenting a political change in Cuba. Then, we study meticulously the ZunZuneo project, detailing its objectives, how it has been conceived and implemented by a variety of public and private institutions, and the audiences for which it is intended. For doing it, we rely on an important corpus of official documents, including declassified ones.